Public spending and economic growth in Latin America countries: A panel fixed effect analysis - Yobouet Thierry Bienvenu Gnangoin; Akadje Jean-Roland Edjoukou; Diby François Kassi (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: This article studies the effects of public expenditure on economic growth in Latin America countries (LAC), especially the role played by foreign aid and public and private investment Design/methodology/approach Granger causality approach and Fixed effect method. Findings: There is bidirectional causality between investment climate improvement, domestic investment and economic growth. Also, private investment, population growth rate, investment climate improvement and corruption reduction lead these countries economic growth. Research limitations/implications: In these countries, to manage economic growth governments have to pay attention on population growth rate , level of corruption, domestic and private investment Originality/value: There are numerous studies regarding the impact of public spending on economic growth, but this study focus on developing countries especially on one area which is Latin America Countries. Also, it shows that ,additionally to private investment ,domestic investment, population growth rate and corruption are economic growth determinants in this area.
Keywords: H52; H54; O47; O54; 330; Public spending; Panel fixed effect; Panel causality test